Pemarkah Kohesi dalam Wacana Berita Karangan Siswa SMP Negeri 2 Jiwan - Fauziyyah Zahra Swandalia; Suparno; Novi Eka Susilowati (Universitas Negeri Malang, 2021)
Abstract: This study aims to describe the cohesion markers used in news discourse written by eighth grade students of SMP Negeri 2 Jiwan. Because the data generated in this study is not in the form of numerical data, but word descriptions and is concerned with language forms, it uses a qualitative approach. This type of research includes discourse analysis research. This study collected the data from students' assignments in the form of news discourses made by graders of SMP Negeri 2 Jiwan which meet the indicators of essay selection. The data elicited are in the form of words, phrases, clauses, and clitics that indicate the use of cohesion markers from news discourse written by the student participants. As the results of the study, the use of grammatical cohesion markers and the use of lexical cohesion markers in students' news discourse are discovered. The results of the study can be used for other related research and can be used as a reference for teachers to improve students' mastery of cohesion markers. Keywords: discourse, cohesion, student essay Abstrak: Penelitian ini bertujuan untuk mendeskripsikan pemarkah kohesi yang digunakan dalam wacana berita karangan siswa kelas VIII SMP Negeri 2 Jiwan. Penelitian ini menggunakan pendekatan kualitatif, hal ini berkaitan dengan data yang dihasilkan berupa deskripsi kata-kata atau bersangkutan dengan bentuk bahasa, tidak berupa data angka. Jenis penelitian termasuk penelitian analisis wacana. Penelitian ini menggunakan sumber data dari tugas siswa berupa wacana berita karangan siswa kelas VIII SMP Negeri 2 Jiwan yang memenuhi indikator pemilihan karangan. Dari sumber data yang didapatkan, diambil data berupa kata, frasa, klausa, dan klitika yang menunjukkan penggunaan pemarkah kohesi dari wacana berita karangan siswa kelas VIII SMP Negeri 2 Jiwan. Hasil dari penelitian ini ditemukan adanya penggunaan pemarkah kohesi gramatikal dan penggunaan pemarkah kohesi leksikal dalam wacana berita karangan siswa. Hasil penelitian dapat digunakan untuk penelitian terkait lainnya dan dapat dijadikan acuan guru untuk meningkatkan penguasaan siswa terhadap pemarkah kohesi. Kata kunci: wacana, kohesi, karangan siswa